Wire loop sinus membrane elevator: a novel instrument for lateral window sinus lift. Issue 12 (December 2020) - Yong, C.W.; Loh, F.C.
Abstract: This technical note introduces a novel instrument to facilitate lateral window sinus membrane elevation. The fabrication and use of the instrument are reported. The features of this instrument include easy control, good tactile sensation, flexibility in adjusting the instrument, and simple to replicate. Since its introduction, it has been the preferred instrument of our implant surgical trainees. Most importantly, it has proved to be an invaluable teaching tool, as it has helped not only to boost trainee confidence in the procedure, but also in their use of other sinus elevation instruments.